Preliminary study of key performance indicators for sustainability in health care industry in Malaysia - Wong, Kuan Lih (2018)
According to the Malaysia Ministry of Health, the health care industry was the fastest-growth industry between 2000 and 2009. This industry is a key driver for the country’s economic growth and has contributed more than RM 1 billion to the national GDP in 2016. In today’s competitive business environment, companies are concerned about improving sustainability within the organization’s infrastructure and performance. Sustainability initiatives are beneficial as they provide an opportunity to a company, not only to reduce cost but also to contribute to the wellbeing of the environment and society. However, there are limited published studies on the evaluation of sustainability performance for the healthcare sector. The aim of this study is to develop a set of key performance indicators (KPIs) and sustainability performance index that can be used to evaluate sustainability performance for the health care industry in Malaysia. This is achieved by 3 objectives: (1) identify key performance indicators for evaluating sustainability performance for primary, secondary, and tertiary industry, (2) propose key performance indicators for evaluating sustainability performance in health care industry, and (3) develop a sustainability performance index for health care industry. First, a literature study of KPIs from various industry namely primary, secondary, and tertiary industries was carried out. Then, a list of KPIs that can be incorporated into health care industry was presented to industrial and academic experts. Next, questionnaires with 70 identified KPIs were distributed to 24 respondents in a private hospital located at Melaka. The results were collected and analyzed using statistic and analytic hierarchy process (AHP). Finally, a sustainability performance index was developed as the evaluation tool for the health care industry. The results were presented to the case company for verification purpose. The outcomes of the study show that the major concern of the private hospital is on the social factor followed by the economic factor and environment factor. The result is not surprising because all private hospitals depend on their patients as main stakeholders; they need to ensure patient satisfaction by providing good quality service which will directly impact the company’s economic growth. In addition, private hospitals have to manage clinical waste products effectively according to the rules and regulations of the country to protect the environment. A performance index was developed to monitor the sustainability performance of the health care industry.